The Association between Dietary Quality Indices and Colorectal Cancer Risk: A Case-Control Study - Elham Tavassoli Nejad; Seyed Mostafa Jalili; Sevda Eskandarzadeh; Milad Rajabzadeh-dehkordi; Mehran Nouri; Bahram Rashidkhani; Zainab Shateri (International Journal of Nutrition Sciences)
Background: Dietary habits have been suggested to play a role in incidence of colorectal cancer (CRC). The current study aimed to evaluate the relationship between dietary patterns (Healthy Eating Index-2015 (HEI-2015) and Dietary Quality Index International (DQI-I)) and CRC risk among Iranian population.Methods: This case-control study was performed in the CRC Surgery Department of Imam Khomeini Hospital enrolling simultaneously 71 participants with CRC as cases and 142 subjects without neoplastic and acute diseases from the same hospital as controls. Participants’ food intake was assessed by a food frequency questionnaire (FFQ). Also, the scores of each of the dietary patterns (HEI-2015 and DQI-I) were classified into tertiles and analyzed.Results: In the crude model, the odds of developing CRC in the third tertile was significantly lower than those in the first tertile of both HEI-2015 (Odds ratio (OR)=0.41; 95% confidence interval (CI)=0.20-0.83) and DQI-I (OR=0.48; 95%CI=0.23-0.98). In the adjusted model, the odds of developing CRC was significantly lower in the last tertile of HEI-2015 (OR=0.37; 95%CI=0.17-0.80) and second (OR=0.45; 95%CI=0.20-0.99) and last tertile of DQI-I (OR=0.30; 95%CI=0.12-0.74) in comparison to the first tertile.Conclusion: A higher score of HEI-2015 and DQI-I was found to be significantly associated with a lower CRC risk. Further prospective studies in diverse populations are recommended to validate these findings.